DIFFERENTIATED SERVICES MODEL WITH GUARANTEED SERVICE - Луцький, М.; Муранов, А.; Муранов, О. (Science-based technologies, 2011)
In accordance with the State Standard of Ukraine ISO 9001, a process approach to the creation of service models intended for use in the systems providing network services on the basis of telecommunication networks is proposed. The models provide the possibility of differential servicing of client-based applications along with corresponding service quality guarantees. The created service models are based on the concept of so-called Telecommunication Service Model of telecommunication networks control structure, supported by MCE-T. The structuring of service processes has been carried out and the interrelation among both processes and telecommunication network operation services supporting these processes has been identified. The processes and their interrelations are represented in corresponding graphs, whose complexes reflect the developed service models.